Use the slope formula below (Rise Over Run)
![\large \boxed{m = (y_2 - y_1)/(x_2 - x_1) }](https://img.qammunity.org/2022/formulas/mathematics/college/fvcfa9pkok03moahqgmi4e8o7ykdjexqkb.png)
We are given two points. Substitute those points in the equation. Remember that it is (x,y) and not (y,x).
![\large{m = (10 - ( - 2))/(3 - ( -1)) } \\ \large{m = (10 + 2)/(3 + 1) \longrightarrow m = (12)/(4) } \\ \large \boxed{\purple{m = 3}}](https://img.qammunity.org/2022/formulas/mathematics/high-school/h0qj2j2k0ginj0felxc9ks6tvkoips4bk2.png)
Next we will be using the point-slope form then convert into slope-intercept form. You can also use the slope-intercept form to substitute one of these points and solve for the y-intercept. However, I will be using the point-slope form instead.
![\large \boxed{y - y_1 = m(x - x_1)}](https://img.qammunity.org/2022/formulas/mathematics/high-school/o7klpejzjcyw5vkok1uexz4yrqk82gyzg9.png)
The equation above is in point-slope form. Next we can substitute one of given points. I will choose (-1,-2) to substitute (You can use another point as well since the outcome would be the same.)
![\large{y - ( - 2) = 3(x - ( - 1))}](https://img.qammunity.org/2022/formulas/mathematics/high-school/yci20e2y2xztfaa800hl0ula8hv70mvhuo.png)
We substitute x1 = -1, m = 3 and y1 = -2. Next, we simplify the equation and convert it in slope-intercept form.
![\large{y + 2 = 3(x + 1)} \\ \large{y = 3(x + 1) - 2} \\ \large{y = 3x + 3 - 2} \\ \large \boxed{ \red{y = 3x + 1}}](https://img.qammunity.org/2022/formulas/mathematics/high-school/5fxxtq7r06z90knx5imqjlht529xbfpwo4.png)
Answer